Analysis The Risk Of Snake Fruit Production Using The House Of Risk Model In Salacca Trading Business - Sri Fatimah Hasibuan; Elita Amrina; Hilma Raimona Zadry (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
The snake fruit processing company UD Salacca faces several challenges in its snake fruit processing activities, including people, machines, methods and the environment. The aim of this research is to identify the challenges faced by UD Salacca in snake fruit production. The risk management method used in this research follows the ISO 31000:2008 guidelines using the House of Risk (HOR) Model, which includes steps for risk identification, risk analysis, risk evaluation, and risk management. 22 risk events (risk factors) have been identified from 9 process activities and 17 risk agents (risk causing factors), of which there are 5 high priority risk causes. The causes of this risk include the mixing process taking less than three hours, weather and pest factors, not being careful when loading, and not being careful in the sorting process using traditional grinding equipment. From the research results, 18 proposed mitigation strategies were found from 9 process activities. Some of the strategies proposed include the use of machines in the ripening process, the use of tools to peel snake fruit, the use of personal protective equipment when working, supervision and implementation of work operational standards during harvest, and the use of assessment checklists when sorting snake fruit. Early handling strategies are needed by salacca businesses to anticipate major risks. These results can be used to increase the company's effectiveness in handling risk management